Severe Malaria Infections Impair Germinal Center Responses by Inhibiting T Follicular Helper Cell Differentiation - Victoria Ryg-Cornejo; Lisa Julia Ioannidis; Ann Ly; Chris Yu Chiu; Julie Tellier; Danika Lea Hill; Simon Peter Preston; Marc Pellegrini; Di Yu; Stephen Laurence Nutt; Axel Kallies; Diana Silvia Hansen (Cell Reports, 2016)
Naturally acquired immunity to malaria develops only after years of repeated exposure to Plasmodium parasites. Despite the key role antibodies play in protection, the cellular processes underlying the slow acquisition of immunity remain unknown. Using mouse models, we show that severe malaria infection inhibits the establishment of germinal centers (GCs) in the spleen. We demonstrate that infection induces high frequencies of T follicular helper (Tfh) cell precursors but results in impaired Tfh cell differentiation. Despite high expression of Bcl-6 and IL-21, precursor Tfh cells induced during infection displayed low levels of PD-1 and CXCR5 and co-expressed Th1-associated molecules such as T-bet and CXCR3. Blockade of the inflammatory cytokines TNF and IFN-γ or T-bet deletion restored Tfh cell differentiation and GC responses to infection. Thus, this study demonstrates that the same pro-inflammatory mediators that drive severe malaria pathology have detrimental effects on the induction of protective B cell responses.